Kemampuan Memproduksi Teks Anekdot Melalui Metode Saintifik Siswa Kelas X Di Kota Mataram - Adha, Isna Diaul; mahsun, Mahsun; Mahyudi, Johan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to measure students' ability in producing text in Indonesian language learning. The focus of this research is to describe the students' ability to write anecdotal texts using scientific methods. The scientific method has been applied for a long time in Indonesia and this research was conducted to see whether the method has been applied properly and brings success to students in improving students' ability to produce text. The population of this research is secondary education students in the city of Mataram and to make the research easier, 113 students were selected as the sample provided that all students have received the same learning. This research is a descriptive normative study with qualitative and quantitative approaches. This research shows that the students' ability in producing literary genre texts goes according to the steps of the scientific method. In conclusion, this study was conducted to see the results of students 'writing skills at the intermediate level after the implementation of the 2013 text-based curriculum in Indonesia with the application of scientific methods and is expected to have success in helping improve students' writing skills in producing a text.